Multisensory enhancement of localization under conditions of induced myopia - Hairston, W. David; Laurienti, Paul J.; Mishra, Gautam; Burdette, Jonathan H.; Wallace, Mark T. (Experimental brain research, 2003)
Enhanced behavioral performance mediated by multisensory stimuli has been shown using a variety of measures, including response times, orientation behaviors, and even simple stimulus detection. However, there has been little evidence for a multisensory-mediated improvement in stimulus localization. We suggest that this lack of effect may be a result of the high acuity of the visual system. To examine whether normal visual acuity may be masking any potential multisensory benefit for stimulus localization, we examined the ability of human subjects to localize visual, auditory and combined visual-auditory targets under conditions of normal and degraded vision. Under conditions of normal vision, localization precision (i.e., variability) was equivalent for visual and multisensory targets, and was significantly worse for auditory targets. In contrast, under conditions of induced myopia, visual localization performance was degraded by an average of 25%, while auditory localization performance was unaffected. However, during induced myopia, multisensory (i.e., visual-auditory) localization performance was significantly improved relative to visual performance. These results show a multisensory-mediated enhancement in human localization ability, and illustrate the cross-modal benefits that can be obtained when spatial information in one sense is compromised or ambiguous.